Biosynthesis, Metabolism and Function of Auxin, Salicylic Acid and Melatonin in Climacteric and Non-climacteric Fruits - Pérez-Llorca, Marina; Muñoz, Paula; Müller, Maren; Munné-Bosch, Sergi (Frontiers in Plant Science, 2019)
Climacteric and non-climacteric fruits are differentiated by its ripening process, in particular by the involvement of ethylene, high respiration rates and the nature of the process, being autocatalytic or not, respectively. Here, we will focus on the biosynthesis, metabolism and function of three compounds (auxin, salicylic acid and melatonin) sharing not only a common precursor (chorismate), but also regulatory functions in plants, and therefore in fruits. Aside from describing their biosynthesis in plants, with a particular emphasis on common precursors and points of metabolic diversion, we will discuss recent advances on their role in fruit ripening and the regulation of bioactive compounds accumulation, both in climacteric and non-climacteric fruits.